Decision Support System for Competition Assessment Using the Analytical Hierarchy Process and Multi-Attribute Utility Theory - Putri Afiifah, Nabiilah; Hidayati, Anita (Intelmatics, 2025)
The advancement of information technology has driven organizations to undergo digital transformation, including in the implementation of competitions. The Informatics and Computer Engineering Student Association (HIMATIK) of Politeknik Negeri Jakarta still uses spreadsheets for registration and judging processes, which are prone to human error, inefficiency, and lack of transparency. This study aims to design and develop a web-based Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) and Multi Attribute Utility Theory (MAUT) methods to improve the quality of judging. The system was developed using Laravel, PHP, MySQL, and front-end technologies such as HTML, CSS, and JavaScript. The user interface was designed using Figma, and the development process followed the Waterfall methodology. AHP was used to determine the weight of the criteria, while MAUT was applied for score calculation and participant ranking. The research approach included qualitative methods and quantitative methods. Black box testing results showed that the system functioned 100% as expected. The System Usability Scale (SUS) score of 89.19 (Excellent category) and a Net Promoter Score (NPS) of 67.5% (Very Good category) indicate a high level of user satisfaction. This system is expected to enhance efficiency, accuracy, and transparency in the judging process and support the digitalization of future HIMATIK activities.